Octahedral ruthenium (II) polypyridyl complexes as antimicrobial agents against mycobacterium - Liao, Guojian (PeerJ, 2017)
Tuberculosis is one of the world’s deadliest infectious disease with 1.5 millions deaths annually. It is imperative to discover novel compounds with potent activity against M. tuberculosis. In this study, susceptibilities of M. smegmatis to the octahedral ruthenium(II) polypyridyl complexes, 1 {[(bpy)(3)Ru] (PF(6))(2) (bpy = 2,2′-bipyridine)}, 2 {[(phen)(2)Ru(dppz)](PF(6))(2) (phen = 1,10-phenanthroline, dppz = dipyridophenazine)} and 3 {[(phen)(3)Ru](PF(6))(2)} were measured by broth microdilution and reported as the MIC values. Toxicities of complex 3 to LO2 and hepG2 cell lines were also measured. Complex 2 inhibited the growth of M. smegmatis with MIC value of 2 µg/mL, while complex 3 was bactericidal with MIC value of 26 µg/mL. Furthermore, the bactericidal activity of complex 3 was dependent on reactive oxygen species production. Complex 3 showed no cytotoxicity against LO2 and hepG2 cell lines at concentration as high as 64 µg/mL, paving the way for further optimization and development as a novel antibacterial agent for the treatment of M. tuberculosis infection.